The impact of Chinese Foreign Direct Investment on economic growth of Peru: a short and long run analysis - Osterloh Mejía, María; Urriola Canchari, Nadia; Deng, Xiangzheng (Latin American Journal of Trade Policy, 2020)
Since 2000, the Peruvian economic policy presented a positive impact on the economic growth thanks to Foreign Direct Investment (FDI) increase and the inclusion of foreign markets in the local economy. This study analyzes and quantifies the short and long-run impact of FDI and Foreign Direct Investment from China (FDICH) on economic growth in Peru, using annual time series data from 2001 to 2018 obtained from the Central Bank of Peru and the World Bank. Vector Autoregression (VAR) Model, Augmented Dickey-Fuller test, Johansen Co-integration test, and Granger Causality test were employed for data analysis through the production function. The findings revealed the impact and significance of FDI and FDICH in the short and long-run, which were positive and significant. Moreover, the Co-integration test (for long-run relationship) was positive, and the causality test in the relationship between all variables and the economic growth revealed the directionality of these links.